Spore evaluated - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
If you were a subscriber to Spore in 1997, you may have participated in the evaluation conducted to assess the relevance and (cost-)effectiveness of Spore, and to work out plans for our future.Questionnaires were distributed to a sample of 7,452...